2019
DOI: 10.1155/2019/5321864
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pelvic Floor Muscles Exercise on Quality of Life in Women with Stress Urinary Incontinence and Its Relationship with Vaginal Deliveries: A Randomized Trial

Abstract: Introduction Urinary incontinence (UI) is a health problem affecting the quality of women's lives (QOL) at various life stages. Stress urinary incontinence (SUI) can be caused by previous vaginal deliveries and is especially likely to occur in the perimenopausal period. The most commonly recommended first-choice treatment methods involve exercises for the pelvic floor muscles (PFM). The aim of this study was to assess the impact of isolated PFM exercises and combined training of the PFM and the m.transversus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 21 publications
3
46
0
3
Order By: Relevance
“…Pelvic Floor physical therapy interventions are not isolated to training of intrapelvic musculature and benefit may be extended when paired with strength training of accessory muscles, such as the gluteal muscles, hip adductors and anterior abdominal wall musculature. Strengthening of the transverse abdominis (TrA)-in addition to intrapelvic musculature-has been shown to decrease effects of SUI and improve quality of life (QOL) in multiparous women [21]. Although pelvic floor physical therapy is available as an option for treating urge urinary incontinence, this is rarely considered in isolation to address and counteract the detrusor contractions [17,22].…”
Section: The Role Of Physical Therapy In Treatment Of Urinary Incontimentioning
confidence: 99%
“…Pelvic Floor physical therapy interventions are not isolated to training of intrapelvic musculature and benefit may be extended when paired with strength training of accessory muscles, such as the gluteal muscles, hip adductors and anterior abdominal wall musculature. Strengthening of the transverse abdominis (TrA)-in addition to intrapelvic musculature-has been shown to decrease effects of SUI and improve quality of life (QOL) in multiparous women [21]. Although pelvic floor physical therapy is available as an option for treating urge urinary incontinence, this is rarely considered in isolation to address and counteract the detrusor contractions [17,22].…”
Section: The Role Of Physical Therapy In Treatment Of Urinary Incontimentioning
confidence: 99%
“…Ptak M et al (2019) compared the Pelvic Floor Muscles (PFM) exercises in isolation and combined with Transversus Abdominis (TrA) training in subjects with SUI [12]. The results demonstrated that PFM + TrA training yielded significantly better results than the (PFM) program.…”
Section: Modern Rehabilitationmentioning
confidence: 99%
“…If SUI is associated with coughing or sneezing, it is categorized as grade I, grade II if SUI is associated with running or picking up heavy objects, and grade III, if the subject has UI while walking or climbing stairs [11]. Overactive bladder syndrome is another urinary problem characterized by urinary urgency accompany with or without urge incontinence, frequency, and nocturia [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods for strengthening the PFMs is a pelvic floor exercise that is also known as Kegel exercises [14,15]. Kegel exercises involve repeated voluntary and selective contraction and relaxation of specific muscles in the pelvic floor [16][17][18].…”
Section: Introductionmentioning
confidence: 99%